Relationship Conflict Management Style With Performance in Nurse in The Special Inpatient Unit of Jemursari Islamic Hospital Surabaya - Imawati, Siti Nurjanah, Riswanda; Santy, Wesiana Heris; Nadatien, Ima; Hanik, Umi; Setyowati, Eppy (International Journal of Psychosocial Rehabilitation, 2020)
Conflicts have occurred in nurse. Almost all nurses have good performance ratings, but there are still nurse who have suf icient performance ratings. This study aims to determine the relationship conflict management style and performance in nurse in the special inpatient unit of Jemursari Islamic Hospital Surabaya. The type of research used is an analytic survey with approach cross-sectional. The population of this study amounted to 114 nurses. The research sample was taken by cluster random sampling with a sample size of 89 people. Data analysis used is an analysis of spearman rank correlation. The results showed that almost all (88.8%) nurses had sufficient conflict management styles and almost all (86.5%) nurses had high performance. The most used style is collaboration (95.5%) and compromise (91.0%). The conflict management style has a relationship with the performance and have a significance value of 0.017. The conclusion of this study is that there is a relationship between conflict management style and performance on nurse in the special inpatient unit of Jemursari Islamic Hospital Surabaya. Suggestions that can be given, namely in resolving conflicts, should nurse use a compromise conflict management style that has the strongest relationship with performance.